Some biological aspects of Mediterranean mud shrimp, Upogebia pusilla (Petagna, 1792) in the Boka Kotorska Bay, Southeastern Adriatic Sea - Marković, Olivera; Đurović, Mirko; Ikica, Zdravko; Huter, Aleksandra (Archives of Biological Sciences, 2023)
Paper description: There is a lack of information on the biology and distribution of Upogebia pusilla (gebiidean mud shrimp) in the south-eastern Adriatic. This study provides new data on the shrimp, including body size, length distribution, sex ratio, allometric growth, and Fulton’s condition factor. The gebiidean mud shrimp is under intense anthropogenic pressure, primarily fishing. The results contribute to general knowledge on this taxon and sustainable management. Abstract: Biological aspects (length frequency distribution, length-weight ratio, sex ratio, allometric growth, Fulton’s condition factor) of Upogebia pusilla were studied in Tivat Saline (Tivatska solila), Boka Kotorska Bay in 2019. A total of 1,415 individuals were collected. The total length of all studied individuals ranged from 27 to 55 mm (8 and 20 mm CL), while the total weights ranged from 0.29 to 2.56 g (the total length of males ranged from 27 to 51 mm, non-ovoid and ovoid females ranged from 27 to 51 mm and 30 to 55 mm, respectively; the weights ranged from 0.29 to 2.52 g, 0.34 to 2.52 g and 0.47 to 2.56 g for males, non-ovoid and ovoid females, respectively). The overall female:male ratio was 1.2:1. Egg-shaped females were recorded from April (74.3%) to June (23.8%), with a peak in May (91.4% of all females). Males dominated in July (66.4%). The relationship between CL and W was negatively allometric in both males and females and in all sampled individuals. Fulton’s condition factor was higher only in females during the breeding season, while there were no significant differences between males and females during the rest of the year. Since this species is mainly used as live bait for commercial and sports fishermen, the results of this study would be useful for the sustainable management of this species.